Adipokines and Sexual Hormones Associated with the Components of the Metabolic Syndrome in Pharmacologically Untreated Subjects: Data from the Brisighella Heart Study - Arrigo F. G. Cicero; Paolo Magni; Massimo Moré; Massimiliano Ruscica; Elena Dozio; Liliana Steffani; Claudio Borghi; Felice Strollo (International Journal of Endocrinology)
We evaluated the association of the sex hormone pattern and the serum level of the main adipokines to metabolic syndrome (MS) and its components in 199 pharmacologically untreated subjects. Men and women included in the age-class subgroups were matched for body mass index, waist circumference, blood pressure, heart rate, fasting plasma glucose, and plasma lipids. Men without MS had significantly lower leptin/adiponectin ratio than men with MS. Women without MS had lower leptin and leptin/adiponectin ratio than women with MS but had significantly higher adiponectin, estrone, and dehydroepiandrosterone levels. In men, the leptin/adiponectin ratio is the main factor associated to MS diagnosis (OR: 3.36, 95% CI 1.40–8.08), while in women adiponectin alone appears to be a protective factor (OR: 0.87, 95% CI 0.79–0.95). In conclusion, in a sample of pharmacologically untreated subjects, leptin/adiponectin ratio seems to be the factor more strongly associated to MS and its components.